2019
DOI: 10.1101/555508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classical conditioning drives learned reward prediction signals in climbing fibers across the lateral cerebellum

Abstract: 27Classical models of cerebellar learning posit that climbing fibers operate according to a 28 supervised learning rule to instruct changes in motor output by signaling the occurrence of 29 movement errors. However, cerebellar output is also associated with non-motor behaviors, and 30 recently with modulating reward association pathways in the VTA. To test how the cerebellum 31 processes reward related signals in the same type of classical conditioning behavior typically 32 studied to evaluate reward processin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 29 publications
5
37
0
Order By: Relevance
“…Further support for non-motor CB roles stems from clinical translational studies, which have linked CB dysfunction with neurodevelopmental disorders, posttraumatic stress disorder, generalized anxiety disorder, addiction, and cognitive and emotional disturbances known as cerebellar cognitive affective syndrome 8,[10][11][12][13][14][15][16][17][18] . These findings are further corroborated by evidence from animal studies, which solidify a role for the CB in the processing of valence, reward, reward anticipation and omission [19][20][21][22][23] ; emotional learning and aggression [24][25][26][27][28][29][30] ; and motivation [31][32][33] .…”
Section: Introductionsupporting
confidence: 60%
“…Further support for non-motor CB roles stems from clinical translational studies, which have linked CB dysfunction with neurodevelopmental disorders, posttraumatic stress disorder, generalized anxiety disorder, addiction, and cognitive and emotional disturbances known as cerebellar cognitive affective syndrome 8,[10][11][12][13][14][15][16][17][18] . These findings are further corroborated by evidence from animal studies, which solidify a role for the CB in the processing of valence, reward, reward anticipation and omission [19][20][21][22][23] ; emotional learning and aggression [24][25][26][27][28][29][30] ; and motivation [31][32][33] .…”
Section: Introductionsupporting
confidence: 60%
“…The probability of a complex spike depends on many factors beyond the presence or absence of a prediction error. For example, while sudden occurrence of a stimulus by itself may not produce a complex spike in the P-cell of a naïve animal, it will do so if the animal has learned to associate that stimulus with an aversive event (Ohmae and Medina, 2015), with a greater reward (Heffley and Hall, 2019;Kostadinov et al, 2019;Larry et al, 2019), or a previous performance error (Junker et al, 2018). Withholding of reward when it was expected can also modulate complex spike rates (Heffley et al, 2018;Kostadinov et al, 2019).…”
Section: Why Do Complex Spikes Carry Information About the Reward Valmentioning
confidence: 99%
“…In summary, several recent reports have shown that complex spikes carry information about the reward value associated with a stimulus (Heffley and Hall, 2019;Kostadinov et al, 2019;Larry et al, 2019). To reconcile this fact with the idea that complex spikes carry an error signal, we can consider an olivary neuron that receives two inputs: inhibition from a DCN neuron, and excitation from a neuron in the superior colliculus.…”
Section: Why Do Complex Spikes Carry Information About the Reward Valmentioning
confidence: 99%
“…An important difference with paradigms generally described in other works (e.g. (Heffley and Hull, 2019;Heffley et al, 2018;Kostadinov et al, 2019;Larry et al, 2019;Tsutsumi et al, 2019)) is that the water delivery was triggered by the first lick of bout, in the moment when the laser beam in front of the lick-port was interrupted; as a result, mice had to lick before the reward was given, so that they could not use the presence of water nor the valve click as a cue. During no-go trials, mice were not supposed to lick and licking was consequently not rewarded.…”
Section: Behavioural Paradigm and Surgical Proceduresmentioning
confidence: 98%
“…The mice had to lick first before they received a reward. The first lick was therefore unrewarded and, given the potential importance of complex spikes for reward expectation (Heffley and Hull, 2019;Heffley et al, 2018;Kostadinov et al, 2019;Tsutsumi et al, 2019), we repeated this analysis while aligning the complex spikes with the second lick, thus the timing of the reward. This did not reveal a clear coupling between the timing of complex spike firing and reward delivery (Fig.…”
Section: Complex Spike Timing Is Most Prominently Linked To Sensory Imentioning
confidence: 99%